Drift in small populations predicts mate availability and the breakdown of self-incompatibility in a clonal polyploid - Cisternas-Fuentes, Anita (The New phytologist, 2024)
© 2024 The Author(s). New Phytologist © 2024 New Phytologist Foundation.